Avaliação do hipotireoidismo em pacientes com leucemia mielóide crônica em tratamento com inibidores de tirosina quinase: associação com biomarcadores de angiogênese e com a resposta ao tratamento - Masullo, Laís Farias (2022)
Chronic Myeloid Leukemia (CML) is a clonal myeloproliferative neoplasm of hematopoietic stem cells. The disease results, in most cases, from the translocation between chromosomes 9:22, forming the BCR-ABL gene that encodes a BCR-ABL oncoprotein with constitutive tyrosine kinase activity. The first-line treatment of CML is with Tyrosine kinase Inhibitors (TKI), which has been shown to be safe, effective and with increased event-free survival. Hypothyroidism has been reported as a complication with potential clinical impact, as it is associated with increased mortality. Thus, it is important to screen for hypothyroidism in patients with CML on chronic TKI use, as well as to investigate the factors associated with this effect. The present study aimed to evaluate the presence of hypothyroidism in CML patients treated with tyrosine kinase inhibitors and to associate it with angiogenesis markers and event-free survival. This is a prospective cohort study including 60 patients diagnosed with CML registered at the HUWC hematology outpatient clinic. The control group included 20 healthy subjects. The analysis of thyroid hormone metabolism was performed by measuring TSH, T4L, T3T and angiogenesis by measuring serum VEGF and expression of the genes: HIF-1a and VEGF. Gene expression analysis were performed by real-time polymerase chain reaction. Clinical and laboratory data, as well as information on the use of the TKI, were obtained from medical records. Statistical analysis was performed using the GraphPad Prism 6.0 program and the tests performed were determined according to the normality of the data. A p-value <0.05 was considered for statistically significant results. Subclinical hypothyroidism was observed in 20% (12/60) of patients diagnosed with CML. Patients had a mean age of 49 ± 21.33 years and the majority (67%; n=8) were male. A moderate correlation was observed between TSH and treatment time in patients with hypothyroidism (R=0.620; p=0.036). When evaluating the event-free survival curve, it was observed that hypothyroidism occurred more frequently in patients using TKI for more than 12 months (p=0.0014). We observed higher levels of serum VEGF (p=0.016) and HIF-1a expression (p=0.0068) in patients with CML when we compared patients in the control group. However, there was no difference in VEGF-A expression between the groups (p=0.20). When comparing the angiogenesis markers between the group with CML and hypothyroidism and the group with euthyroid CML, there was no difference between them: serum VEGF (p=0.23); HIF-alpha (p=0.14) and VEGF-A (p=0.52). Furthermore, no association was observed between the clinical variables of CML and the presence of hypothyroidism when the event-free survival was analyzed. Conclusion: Subclinical hypothyroidism was present in patients with CML using TKI, however, the same cannot be attributed to the treatment. In addition, angiogenesis markers were not associated with hypothyroidism. It is also noteworthy that the finding of hypothyroidism was not associated with a worse prognosis.